Manajemen Madrasah Diniyah Fathul Ulum Puton Diwek Jombang - Nurul Indana; Munardji Munardji; Kojin Kojin (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2023)
Recognition of Religious Education in the National Education system, of course, will also demand an increase in the management of Religious Education institutions. The implementation of Madrasah Diniyah is accompanied by maximum planning, organizing, implementation, and supervision so that management in educational institutions is getting better and of higher quality. Based on the description above, the management of madrasah diniyah is an important matter to study. This research is a libraryresearch, with data collection techniques through interviews, observation and documentation, using data analysis and triangulation. The results showed that the management of Madrasah Diniyah Fathul 'Ulum Puton Diwek Jombang can be seen from the planning, organizing, movement and supervision. Planning is carried out in consultation with the caretaker of the cottage with the diniyah administrators as well as the ustadz. This plan focuses on the material or program being taught, the management of the madrasah madrasah, as well as the learning process for the madrasah madrasah. Organizing is done by creating an organizational structure according to the abilities possessed. This organizational structure was created to facilitate the implementation of madrasah diniyah. The movement can be seen from the activities of the madrasah diniyah every day which basically contain tafaquh fiddin activities, tahfidzul qur'an and entrepreneurial activities. And supervision is carried out by the head of the madrasah diniyah both vertically and horizontally to control how far this madrasah is running.